(untitled) (Stamford Journal of English, 2013)
The main objective of teaching vocabulary in EFL classes is to empower the learners with sufficient word stock for successful communication. Observations show, for both EFL instructors and learners (of Bangladesh), vocabulary acquisition is an important but tiring task as in most of the cases learners need to memorize blindly lengthy word lists suggested by their instructors as a practice of vocabulary learning. But in their real life communication, learners could rarely use any word that they have been taught as vocabulary items in language classes because only dependency on memorization cannot serve them properly with the right word/s at times of their needs. This study critically analyzes the reasons that makes vocabulary related tasks done in EFL classes mostly unsuccessful and suggests some recommendations that could come in help for achieving an improved outcome. Though the study is done focusing the context of Bangladesh, the picture is more or less common in all EFL contexts. Therefore, the recommendations are applicable anywhere where ESL /EFL Vocabulary acquisition is the concern. Stamford Journal of English; Volume 6; Page 54-71 DOI: http://dx.doi.org/10.3329/sje.v6i0.13902